Patterns of Interstate Migration in the Mid-2000s: Are Racial Groups Moving in Different Directions? - Charles Jaret; Jim Baird (Journal of Public and Professional Sociology)
This research examines interstate in-movement, out-movement, and resulting patterns of net internal migration of Blacks, Asians, Hispanics, and non-Hispanic Whites in the United States, using data from the 2005-2007 American Community Survey. One goal is to learn how similar or dissimilar members of these four broad racial categories are in entering and exiting different U.S. states, and thereby to contribute to ongoing research on differential spatial relocation of racial groups (e.g., are these groups moving to different sets of states?). A second goal is to learn how Black, Asian, Hispanic, and White net internal migration levels correlate with economic, demographic, and social characteristics of the states. Results show that similarities in patterns of Black, Asian, Hispanic, and White in-, out-, and net migration overshadow differences. For each race the states with high (or low) numbers and rates of in- and out-movement are largely the same. White and Hispanic interstate mobility patterns show the greatest similarity, Black and Asian the least. Moreover, these racial categories resemble each other in how their net internal migration correlates with economic and social characteristics of U.S. states. Results also suggest regional variation: in the South, states with economic and social characteristics indicative of higher “development” have higher net internal migration for all races, but in the North those states with higher development characteristics have lower (often negative) net internal migration.